The Role of Public Service Centers in Shaping Community Waste Management Behavior in Ambon City - Alwi Smith; Ayu Christine Rahaweman; Eifan Boyke Pattiasina (Publisia: Jurnal Ilmu Administrasi Publik, 2026)
Generally, the waste management has to involve the entire society component, not only the government but also the society itself. The government can be useful with their regulation and their productive programs related to waste management. But the regulation and the program can only be successfully applied if the society actively takes part in the grand plan designed by the government. In this paper, we analyzed the influence between the waste facility provide by the government, self-knowledge of the society about waste management and society figure who can be a role model in managing the waste to the society behavior of waste self-management in Ambon Moluccas. This research showed that only 23.83% of the society behavior of waste self-management in Ambon Moluccas can be analyzed through the variables of waste facility, self-knowledge and society figure simultaneously. Furthermore, it is also shown us that the Society behavior variable can be explained 17.53% by the waste facility variable, 14.19% by the self-knowledge and 1.63% by the society figure particularly.